2019
DOI: 10.1021/acsanm.9b01580
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conductive Films Derived from Single-Walled Aluminosilicate Nanotubes

Abstract: This study reports on an approach to enhancing the performance of silver nanowire (AgNW)-based transparent conducive films (TCFs) via introducing an emerging class of nanotubes, aluminosilicate nanotubes (AlSiNTs), which can reduce silver ions to form silver nanoparticles (AgNPs). This reaction was performed in a suspension of AlSiNTs and AgNO3(aq) under ambient conditions, i.e., without the need for additional reducing agents. The results of material characterization suggest that the AlSiNTs collapse after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…33,34 In this sense, stable dispersion of nanoparticles immobilized on imogolite nanotubes have been obtained either by combination of preformed carboxylato-modified gold NPs 35 or by reducing metallic salts in situ in the host dispersion. [36][37][38][39] However, none of these studies reported the self-organization of the resulting hybrid system in LC phases. We hypothesize that methods limiting the uses of molecular additives would address this issue.…”
Section: Metal-oxide Imogolite Nanotubes (Ints) With Chemical Composition (Oh) 3 Al 2 O 3 (Ge 1-mentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 In this sense, stable dispersion of nanoparticles immobilized on imogolite nanotubes have been obtained either by combination of preformed carboxylato-modified gold NPs 35 or by reducing metallic salts in situ in the host dispersion. [36][37][38][39] However, none of these studies reported the self-organization of the resulting hybrid system in LC phases. We hypothesize that methods limiting the uses of molecular additives would address this issue.…”
Section: Metal-oxide Imogolite Nanotubes (Ints) With Chemical Composition (Oh) 3 Al 2 O 3 (Ge 1-mentioning
confidence: 99%
“…Metal-oxide imogolite nanotubes (INTs) with chemical composition (OH) 3 Al 2 O 3 (Ge 1– x Si x )­(OH) offer many advantages as a host structure compared to other nanotubes . Synthesized in aqueous media, they readily form nematic and hexagonal columnar phases at low volume fractions (<1%), which can be related to excluded-volume effects and the large intensity of repulsive interactions. , The high density of hydroxyl groups (∼18 OH/nm 2 ) offers a high affinity for immobilization of metallic NPs on the outer surface. , In this sense, stable dispersion of nanoparticles immobilized on imogolite nanotubes has been obtained either by combination of preformed carboxylato-modified gold NPs or by reducing metallic salts in situ in the host dispersion. However, none of these studies reported the self-organization of the resulting hybrid system in LC phases. We hypothesize that methods limiting the uses of molecular additives would address this issue.…”
mentioning
confidence: 99%
“…[17,18] In addition, the synthesis process is relatively straightforward, enabling to control the morphology (single vs double-walled structures, aspect ratio…) and the surface properties of the inner cavity by changing the nature of the precursors. [19][20][21] Thanks to their unique colloidal properties, [22] INTs have demonstrated their ability to effectively stabilize metal nanoparticles on their external surface [23][24][25] but, to date, the growth of semiconductor nanowires with INTs has not been truly explored.…”
Section: Introductionmentioning
confidence: 99%
“…For the fabrication of transparent electronic devices, such as touchscreen panels (TSPs) and flat-panel displays (FPDs), it is essential to develop transparent conductive electrodes (TCEs) with high transmittance and low resistivity. Although indium tin oxide (ITO) has been mainly applied as a typical material for TCEs in electronic devices because of its high figure of merit and good compatibility with conventional semiconductor-processing technology [ 1 , 2 , 3 ], the demand for developing new TCE materials with better conductivity has been soaring as the sizes of TSPs and FPDs increase continuously [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%